Comparison of muscle strength asymmetry between field- and court-sport athletes - Thomas, C.; dos Santos, T.; Comfort, P.; Jones, P. A. (Sport Performance & Science Reports, 2017)
Muscle strength asymmetry (MSA) refers to the relative strength differences between limbs (1). It is suggested asymmetries are training- and competition-history specific, thus athletes may develop MSA in part due to handedness, previous injury or execution of repetitive unilateral and asymmetrical movements (2). Furthermore, it is still not known whether sporting background or gender influences MSA values, which may have implications for diagnosis of MSA and resultant training interventions. Aim. The purpose of this report was to examine the differences in MSA in various muscle strength qualities between soccer, cricket and court-based athletes.